The Florida Natural Resources Leadership Institute - Paul Monaghan; Emily Ott; Carol Lippincott; Ondine Wells; Jessica Ireland; Jon Dain; Bruce Delaney; Roy Carriker (EDIS, 2014)
We are all dependent on Florida’s natural resources for jobs, health, and our quality of life. Decisions about the management and conservation of the State’s environment involve complex sets of issues and stakeholders. Expensive and time-consuming disputes often emerge over topics such as endangered species, land use, coastal and marine resources, and water quality and quantity. Effective leadership in managing such issues requires a specialized set of skills, tools, and strategies to build trust and promote innovation and collaboration among competing interests. To meet these needs, the Florida Natural Resources Leadership Institute (NRLI) was founded in 1998 to bring together professionals and stakeholders from diverse natural resource sectors to develop the skills required to engage the public and one another in collaborative decision-making. This revised 4-page fact sheet was written by Paul Monaghan, Emily Ott, Carol Lippincott, Ondine Wells, Jessica Ireland, Jon Dain, Bruce Delaney, and Roy Carriker, and published by the UF Department of Food and Resource Economics, December 2014.